Measuring Anxiety Level of Learning English Language among Refugee Teenagers in Malaysia - Abadi, Mansurni; Shalihah, Ma’aratuni Binti Haji; Ramdani, Suciati Binti Haji; Vladoui, Isabelle Emiral (Universitas Muhammadiyah Mataram, 2022)
Owing to legislative restrictions, Malaysia cannot provide education for refugee children. Instead, the state invites numerous parties, including NGOs, to construct alternative refugee schools. Because education for refugees is an alternative, the goal is directed at practical skills to help refugees work and integrate with Malaysian society or the following country for future resettlement. All of Malaysia's alternative schools for refugees place a strong emphasis on English language acquisition. Even with free education, refugee children struggle to learn English as a Second Language. Psychological phenomena, such as language anxiety, trigger obstacles in learning English. However, learning about language anxiety in the context of alternative education in Malaysia has rarely been studied. Using the mixed-method methodology (MMR) brings about post-positivism and interpretivism. This study had two goals: (1) bridging research gaps on anxiety in learning English as a second language from the viewpoint of alternative school actors and students in refugee communities, and (2) providing solutions for alternative education for refugee communities in Malaysia to understand and address foreign language anxiety. Our study focuses on refugee students from three alternative schools in Klang Valley: the United Learning Center (ULC), Save School Malaysia, and Refugee Academy. The quantitative technique used 92 students to complete the English Language Classroom Anxiety Scale (ELCAS), derived from the Foreign Language Classroom Scale (FLCAS). In addition, we interviewed two persons and one teacher from each school for the qualitative approach. For data analysis, we used SPSS 19 for a quantitative and interpretive approach to the qualitative data. Qualitative results indicate that refugee children from three Klang Valley alternative schools experienced medium foreign language learning anxiety. Most refugee children were anxious about English courses, regardless of gender or stream group, emphasizing the necessity for educators and other stakeholders to understand refugee children's anxiety levels and take action with extensive knowledge of anxiety and compassion. Counselors must also work with teachers to create interventions to assist refugee children in handling their anxiety while studying English. Finally, instructors must use fascinating teaching approaches to minimize refugee children's anxiety, motivate them with empathy and compassion, and avoid overcorrection.